E‐Books and E‐Book Apps: Considerations for Beginning Readers. (12th November 2016) - Bates, Celeste C.; Klein, Adria; Schubert, Barbara; McGee, Lea; Anderson, Nancy; Dorn, Linda; McClure, Erin; Ross, Rachael Huber
Abstract: This article highlights considerations for teachers when selecting and using e‐books and e‐book applications (apps) with beginning readers during guided and independent reading. A framework for examining e‐books and e‐book apps is suggested, and several apps and related digital features are described. The article also includes an overview of children's emergent and early reading behaviors, the types of texts that support these behaviors, and examples of how digital texts could influence beginning reading instruction. Also discussed are the ways in which e‐books and e‐book apps can enhance the home–school connection and support English learners.